Effects of Teachers' Self-Efficacy Perception on Computer Assisted Teaching Perception - Korumaz, Mithat; Karabiyik, Belkis (ELSEVIER SCIENCE BV, 2014)
The aim of the study is to investigate the effects of teachers' self efficacy level on their perceptions of computer assisted teaching. This is a quantitative and descriptive study. In this study 131 teachers from different branch of science and level were selected by random sampling. In the study Self-Efficacy Perception Instrument developed by Gulebaglan (2003) and Computer Assisted Teaching Perception Instrument developed by Arslan (2006) were used. Independent Sample T-test, One-way ANOVA, Kruskal Walls-H, Mann Whitney U and Pearson Correlation tests were used to analyze data. As a result of the study there is a significant and positive relationship between perception of teachers' who study in different branch of science and teachers' computer use level. Additionally there is a significant difference according to the type of institution in which teachers work. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Self-efficacy; Computer Assisted Teaching; BELIEFS; Education & Educational Research